Dimensional Measurement of Small Hot Pieces Based on a Monochrome CCD. (2015) - Chao, Bi; Xinghua, Qu; Yong, Liu; Yaping, Liu; Jingliang, Liu
Abstract: For the purpose of controlling the quality of forging process, a low-pricedmonochrome CCD is adopted to establish avision measurement systemto gauge the two-dimensional sizes of hot parts accuratelyin the paper. To derive the two dimensions of the forgings, comparison measurement method is employed. In the system, images are taken by the CCD through an infrared filter to filter out the strong light emitted from the forgings. And thenaverage filtering and morphological filtering are used to reduce the effect of image noise. In order toimprove the precision of geometry position, image distortion is corrected to reduce theoptical distortion errors. After that, the edges in images are extracted at sub-pixel level to improve the location accuracy of geometry features. After calibration, the horizontal equivalent size of a pixel is 0.119 mm, while the vertical 0.120 mm. As be verified, the horizontal measurement uncertainty is 0.0069 mm, while vertical 0.0063 mm. Images of a 45 # steel cuboid at 1000°C are captured and its dimensionsare calculated through the procedure described in the paper, which have a difference less than 0.5 mm compared with the theoretical values, indicating the precision and practicality of the method proposed in the paper.